Respiratory monitoring during less invasive surfactant administration in the delivery suite. (March 2021) - Ambulkar, Hemant; Williams, Emma E.; Hickey, Ann; Bhat, Ravindra; Dassios, Theodore; Greenough, Anne
Abstract: Background: On the neonatal unit less invasive surfactant administration (LISA) reduces BPD and the need for mechanical ventilation. Aims: To evaluate the feasibility of LISA in the delivery suite and to undertake respiratory function physiological monitoring before and after LISA. Study design: A prospective, observational cohort study was undertaken. A LISA simulation training programme was delivered. Then, LISA was undertaken in infants with respiratory distress maintained on continuous positive airway pressure (CPAP) in the delivery suite using videolaryngoscopic guidance without sedation. Subjects: Thirty-eight infants with a median (IQR) gestational age of 31 + 5 weeks (30 +3 –33 +4 ) and birth weight of 1.61 (1.42–1.90) kg had LISA in the delivery suite. Outcome measures: Adverse effects of LISA and whether LISA resulted in changes in tidal and minute volumes, end tidal carbon dioxide (EtCO2 ) levels and the inspired oxygen concentration (FiO2 ). Results: Respiratory function monitoring was available for 34 of the infants. LISA occurred at a median (IQR) interval of 18 (15–29) minutes after birth. The most common adverse events were desaturation (44.7%) and surfactant reflux (39.5%), both responded to either temporary suspension of LISA or slowing the speed of surfactant administration. Following LISA, there was a significant reduction in respiratory rate 2 min later ( p < 0.001) and in the FiO2 2 h later (p < 0.001). Conclusions: LISA is feasible in the delivery suite after appropriate training of staff. It can be undertaken without serious adverse effects and results in a reduction in respiratory distress and improvement in oxygenation. Highlights: Less invasive surfactant administration (LISA) on the NICU reduces BPD. LISA was undertaken in the delivery suite in infants with respiratory distress. There were no serious adverse events. Desaturations and surfactant reflux responded to slowing the administration speed. LISA was associated with improvements in oxygenation and less respiratory distress.